2014
DOI: 10.12980/apjtb.4.2014c423
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based identification of methicillin–resistant Staphylococcus aureus strains and their antibiotic resistance profiles

Abstract: This study is suggestive that the PCR for detection of mecA gene is a fast, accurate and valuable diagnostic tool, particularly in hospitals in areas where methicillin-resistant S. aureus is endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 18 publications
5
55
2
1
Order By: Relevance
“…PCR based identification of methicillin resistant S. aureus strains and their antibiotic resistance patterns were evaluated by Pournajaf et al (2014). Among antibiotics used in their study, penicillin showed the least activity against S. aureus and vancomycin was the most effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR based identification of methicillin resistant S. aureus strains and their antibiotic resistance patterns were evaluated by Pournajaf et al (2014). Among antibiotics used in their study, penicillin showed the least activity against S. aureus and vancomycin was the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…There are several phenotypic methods for detection of microorganisms' antimicrobial susceptibility patterns, which however are not discriminating enough. So, it is essential to use more rapid and accurate methods like PCR for identification of staphylococci and their resistance patterns (Pournajaf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Two tests were used to identify the type of bacteria namely; coagulase and catalase [14]. The identification of S. aureus suspicious grown colonies was based on gram staining and standard biochemical reactions, including catalase and coagulase [15].…”
Section: Methodsmentioning
confidence: 99%
“…The multiplex PCR method is a rapid, accurate, and useful assay to detect the mecA gene in MRSA strains, particularly in a hospital setting (25).…”
Section: Multiplex Pcr Assay For Assignment Of the Mec Element Typementioning
confidence: 99%